Healthcare resource utilization and caregiver burden associated with rotavirus gastroenteritis hospitalizations in Taiwan - Yhu-Chering Huang; Chih-Hsien Chuang; Chia-Jung Hsieh; Chiu-Mei Hsieh; Ying Hui Wu; Questa Lin; Joanne Lin; Fei Qin; Janine Verstraete; Michael Herdman; Cristina Carias (BMC Pediatrics)
Abstract Background Rotavirus infection is a leading cause of acute gastroenteritis in children aged < 5 years. However, few studies assessed the spillover effect on caregivers’ health-related quality of life (HRQoL) and out-of-pocket costs associated with rotavirus gastroenteritis (RGE) in Taiwan. Methods This is a prospective, observational, survey-based study conducted in Northern Taiwan between March 2021-September 2023. Caregivers were interviewed during the RGE-hospitalization episode and after patient discharge. One caregiver per child aged ≤ 9 years with clinical presentation of a new RGE hospitalization was enrolled. Outcomes assessed included caregiver HRQoL, emotional state, impact on daily routine, healthcare resource utilization (HCRU), and direct and indirect costs. Results The mean age of inpatients was 3.03 years and 69.0% were male. Rotavirus genotype G3P[8] was detected in 61.2% of patients. Caregivers' mean age was 33.7 years, 79.3% were female, and 65.5% had monthly household income < NT$80,000. Caregivers reported significantly higher health state (EQ visual analog scale) after discharge (86.21) than during RGE hospitalization (74.48) (p = 0.049). Among the caregivers, 65.5% and 69.0% experienced disruptions in sleep and leisure activities, respectively. About 45% were worried about complications and 41.4% were concerned about their child’s recovery. The total medical costs associated with hospitalization, reimbursed by National Health Insurance, averaged US$575.56. Additional out-of-pocket costs included US$82.51 for medical visits, US$44.95 for transportation, US$5.47 for medication, and US$90.41 for meals outside the home. The caregivers also reported taking an average of 0.12, 1.18, and 1.82 days of child/parental, paid, and unpaid leave, respectively. The estimated wage loss associated with the days not working was US$246.67. Conclusion RGE poses a significant burden on caregivers’ HRQoL, daily activities, and out-of-pocket costs. Interventions aimed at mitigating the spillover effects of RGE on caregivers are essential to improve family well-being. Clinical trial number Not applicable.